Thoughts about Democracy and Schools - Davies, Don (International Journal about Parents in Education, 2023)
Some of the ideas in these comments are drawn from one of the chapters I wrote for in Beyond the Bake Sale. Please, understand that I don’t intend to offer here a formal scholarly paper that could pass any vigorous review by ERNAPE. I simply offer some personal and informal ideas. I am also not going to offer examples and how-to- do-it tips or research results as these are all available in the Bake Sale book that my colleagues and I have put forward and in its new Portuguese sibling (entitled A Escola também se vive cá fora) or in hundreds of other books on-line and in print, and reports and the papers from this and earlier ERNAPE conferences.